2006
DOI: 10.1063/1.2195368
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of La-doped BiFeO3 thin films with Fe2+ ions on Si substrates

Abstract: La-doped BiFeO 3 thin films with Fe 2+ ions have been prepared on Pt/ TiO 2 / SiO 2 / Si substrates by pulsed laser deposition in order to enhance the ferroelectric and magnetic properties. The targets for the film deposition were synthesized using a rapid liquid phase sintering technique to ensure the low leakage. The dielectric properties at room temperature and above were investigated. It was observed that the La doping greatly enhances the ferroelectric polarization at room temperature by modifying the fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 28 publications
6
50
0
Order By: Relevance
“…The P-E loops exhibit leaky feature which is quite usual for SP multiferroic systems [9]. This leakage-related contribution was also confirmed in earlier reports [14,27,28] and seems to be intrinsic. As for undoped BTF [14] and Co-doped BTF [28] systems the positive-up-negativedown measurements confirmed that the ferroeletricity of BTF systems, although leaky, is intrinsic and natural and the leakage current does not play a big role in the ferroelectric behavior.…”
Section: Resultssupporting
confidence: 80%
“…The P-E loops exhibit leaky feature which is quite usual for SP multiferroic systems [9]. This leakage-related contribution was also confirmed in earlier reports [14,27,28] and seems to be intrinsic. As for undoped BTF [14] and Co-doped BTF [28] systems the positive-up-negativedown measurements confirmed that the ferroeletricity of BTF systems, although leaky, is intrinsic and natural and the leakage current does not play a big role in the ferroelectric behavior.…”
Section: Resultssupporting
confidence: 80%
“…The typical P-E loops although somewhat leaky have been observed. This leakage-related contribution was also confirmed in earlier reports [17,19,21] and seems to be intrinsic. However, as for BTF [19] and Bi 5 Ti 3 Fe 0.5 Co 0.5 O 15 [17] systems, the positive-up-negative-down measurements confirmed that the ferroelectricity of BTF systems, although leaky, is intrinsic and natural and the leakage current does not play a major role in the ferroelectric behavior.…”
Section: Methodssupporting
confidence: 88%
“…We chose BLF rather than BFO as our target of study because our major motivation is to prepare high-quality FEM thin films of both FE and FM orders at RT. A doping of 20% at La was proven to benefit most to the magnetic performance and ME coupling without scarifying much the electrical resistivity [6,22]. In addition, we also studied the effect of ambient pressure for deposition on the quality of BLF thin films, and found that the samples deposited at an ambient pressure as low as 1.0 Pa would have resulted in serious electrical leakage while no much change in the magnetic property was observed.…”
Section: Introductionmentioning
confidence: 96%